The source craters of the martian meteorites: Implications for the igneous evolution of Mars - Herd, C.D.K.; Hamilton, J.S.; Walton, E.L.; Tornabene, L.L.; Lagain, Anthony; Benedix, Gretchen; Sheen, A.I.; Melosh, H.J.; Johnson, B.C.; Wiggins, S.E.; Sharp, T.G.; Darling, J.R. (2024)
Approximately 200 meteorites come from ∼10 impact events on the surface of Mars, yet their pre-ejection locations are largely unknown. Here, we combine the results of diverse sets of observations and modeling to constrain the source craters for several groups of martian meteorites. We compute that ejection-paired groups of meteorites are derived from lava flows within the top 26 m of the surface. We link ejection-paired groups to specific source craters and geologic units, providing context for these important samples, reconciling microscopic observations with remote sensing records, and demonstrating the potential to constrain the ages of their source geologic units. Furthermore, we show that there are craters that may have produced martian meteorites not represented in the world's meteorite collections that have yet to be discovered.